2005
DOI: 10.1080/10284150500170799
|View full text |Cite
|
Sign up to set email alerts
|

Effects of theanine, r-glutamylethylamide, on neurotransmitter release and its relationship with glutamic acid neurotransmission

Abstract: t Theanine, r-glutamylethylamide, is one of the major amino acid components in green tea and many researchers have compared theanine's effects with glutamic acid because the chemical structure is similar. In the previous study, we demonstrated that theanine can pass brain-blood barrier and may play as an agonist or an antagonist of some receptors. In this study, we investigated the effects of theanine on neurotransmitter release in the rat brain striatum by in vivo brain microdialysis and examined whether thea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 51 publications
1
42
2
2
Order By: Relevance
“…From these reports, we suggested that theanine did not stimulate glutamate neurotransmission directly. Thus, next, we supposed that theanine would block glutamate transporters and glutamic acid density would increase in the interstitium and enhance glutamic acid neurotransmission because some reports suggested that theanine affects glutamate transporters (Sazduka et al 2001); however, our results showed that theanine did not affect glutamate transporters (Yamada et al 2005). In addition, we found that theanine enhanced glycine perfusate concentrations in the previous study; therefore, we considered that theanine released inhibitory neurotransmitters.…”
Section: Introductioncontrasting
confidence: 53%
See 1 more Smart Citation
“…From these reports, we suggested that theanine did not stimulate glutamate neurotransmission directly. Thus, next, we supposed that theanine would block glutamate transporters and glutamic acid density would increase in the interstitium and enhance glutamic acid neurotransmission because some reports suggested that theanine affects glutamate transporters (Sazduka et al 2001); however, our results showed that theanine did not affect glutamate transporters (Yamada et al 2005). In addition, we found that theanine enhanced glycine perfusate concentrations in the previous study; therefore, we considered that theanine released inhibitory neurotransmitters.…”
Section: Introductioncontrasting
confidence: 53%
“…Some of these reports also suggested that theanine is concerned with glutamate receptors, although the affinity of theanine to glutamate receptors was low (Kakuda et al 2002a). From these results and a report that dopamine release is enhanced when glutamic acid is increased in the interstitium (Globus et al 1988;Moghaddam et al 1990), we expected that the effect of theanine would be similar to that of glutamic acid, i.e., enhancing excitatory neurotransmission or increasing glutamic acid release from neurons; however, we showed that theanine did not affect glutamic acid and aspartic acid release from neurons (Yamada et al 2005). In addition, other reports showed that the effects of theanine differ from those of glutamic acid; for instance, theanine decreased blood pressure in a dosedependent manner in spontaneously hypertensive rats (SHR) (Yokogoshi et al 1995), but glutamate did not exhibit antihypertensive action on SHR.…”
Section: Introductioncontrasting
confidence: 46%
“…The substrate specificity of GCS was assayed as follows: The 0.2 ml reaction mixtures contained 15 mM ATP, 100 mM MgSO 4 , 5 g/l MSG, 2 or 10 g/l amines, and 100 mg/l (His) 6 -tagged GCS in 0.1 M Tris-HCl buffer (pH 8.5). The reaction was carried out at 37 C for 60 min, and was stopped by boiling at 100 C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…1) Besides its graceful flavor, many physiological functions of it have been reported, including mind relaxation, 2) improvement in sleep disturbances, 3) suppression of blood pressure elevation, 4) anti-oxidation of LDL cholesterol, 5) modulation of neurotransmission, 6) neuroprotection, 7) anti-hypertension, 8) enhancement of antitumor activity, 9) and improved recognition. 10) In the tea plant, theanine is synthesized by theanine synthetase (EC 6.3.1.6), with Glu, ethylamine, and ATP as substrates, 11) but it is very labile, so it cannot be used in industrial theanine production.…”
mentioning
confidence: 99%
“…4) Other reports have indicated that theanine binds to glutamate receptors and mediates glutamate neurotransmission. 5,6) Glutamate is a major neurotransmitter in mammals, and the stimulus it gives is very important in learning and memory, 7,8) but, there have been few reports about the effect of theanine on behavior in instance learning and emotion. Behavior tests relating to learning and memory have been adopted in recent studies, such as the Morris water maze test and the passive avoidance test, but these tests involve various factors, such as fear and locomotor activity.…”
mentioning
confidence: 99%